Comparison of different definitions to classify remission and sustained remission: 1 year TEMPO results. Issue 11 (28th April 2005) - van der Heijde, D; Klareskog, L; Boers, M; Landewé, R; Codreanu, C; Bolosiu, H D; Pedersen, R; Fatenejad, S
Abstract : Objective: To assess methods to calculate achieving and sustaining remission in a double blind randomised trial in patients with RA who received etanercept, methotrexate, or an etanercept/methotrexate combination. Methods: Remission was defined as DAS <1.6, DAS28 <2.6, and ACR70 response. Sustaining remission was analysed in three ways: ( a ) analysis of sustained DAS remission, DAS28 remission, or ACR70 response continuously for 6 months; ( b ) analysis of sustained remission appraised through a continuity rewarded scoring system, which is the weighted sum of all intervals in the study in which patients are in DAS or DAS28 remission; or ( c ) longitudinal modelling of remission odds using generalised estimating equations. Results: Significantly more patients treated with the etanercept/methotrexate combination reached DAS remission (37%) than those treated with either methotrexate (14%) or etanercept (18%) alone (p<0.01). Results for DAS28 and for the ACR70 response were similar. Agreement between DAS remission and DAS28 remission was good, but agreement between either of these and the ACR70 response was less. Patients in DAS or DAS28 remission had a lower level of disease activity (fewer active joints, lower ESR) than those achieving ACR70 response; the converse was seen using pain VAS. The three methods were comparable for sustainability of remission and showed significant advantage for combination therapy, which increased the number and durability of remission periods. Conclusions: DAS and DAS28 remission results were similar for assessing achieving and sustaining remission in RA, frequently differing from patients classified as ACR70 responders. The three methods of examining duration of remission produced comparable results.